PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING DALAM BENTUK STRATEGI QUESTION STUDENTS HAVE TERHADAP KOMPETENSI BELAJAR BIOLOGI SISWA KELAS XI SMAN 1 BAYANG - Kurniasih, Yulvina; Sumarmin, Ramadhan; Anhar, Azwir (Kolaboratif, 2015)
The low biology learning competence of the students in this research due to the teacher centered learning process, so that students do not understand the concept, less active in the discussions, embarrassed to ask, and less teamwork in the group. One of the efforts made to help students to solve the learning problem is by using the model of Problem Based Learning in the form of Question Student have strategy. The population of the study was a class XI students of SMAN 1 Bayang, registered in the first semester of the school year 2014/2015. The Sampling was done by using purposive sampling technique. This study was an experimental study by using design factorial 2 x 2, which PBL model in the form of QSH strategy as independent variables, initial knowledge as a moderator variable, and learning competencies as the dependent variable. The knowledge Instruments used is the objective test of 40 items that have been tested. The observer sheet for attitudes instruments and skills instruments to see the students' learning competencies in experimental class and control class. The results showed that: (1) The average value of students' knowledge competence in experimental class was higher than the control class (2) The average value of knowledge competency based on the high prior knowledge, experimental class was higher than the control class (3) The average value competency of knowledge based on the low intial knowledge of the students, experimental class students was higher than the control class (4) The average value of students' attitudes competence, experimental class was higher than the control class (5) The average value of competence skills, experimental class students was higher than the control class (6) There was no interaction of the learning model with the prior knowledge.